2005
DOI: 10.1007/s11205-005-7525-9
|View full text |Cite
|
Sign up to set email alerts
|

Spillover Between Work Attitudes and Overall Life Attitudes: Myth or Reality?

Abstract: It is widely believed that work attitudes influence attitudes toward life overall. We investigated a multivariate model of work attitudes and overall life attitudes using survey data from two nationally representative (U.S.) data sets, one cross-sectional and one longitudinal. Including a comprehensive set of control variables, we found only weak support for the "attitudes spillover" perspective, suggesting that employees often compartmentalize or "segregate" their work and nonwork lives. We consider theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Using working conditions, living conditions, job satisfaction and non-work satisfaction (an index created from thirteen other life-domains) to predict life satisfaction, they found job satisfaction to be a weak predictor of life satisfaction compared with non-work satisfaction. An additional study by Rode and Near (2005) found that job satisfaction was positively related to overall life satisfaction; this relation emerged when variables concerning work characteristics (inter alia, working hours) and demographic characteristics were controlled for. Using a domains-of-life approach, our study explores the importance of work-related variables in explaining overall life satisfaction in 28 EU countries, 2011-2012.…”
Section: 1mentioning
confidence: 94%
“…Using working conditions, living conditions, job satisfaction and non-work satisfaction (an index created from thirteen other life-domains) to predict life satisfaction, they found job satisfaction to be a weak predictor of life satisfaction compared with non-work satisfaction. An additional study by Rode and Near (2005) found that job satisfaction was positively related to overall life satisfaction; this relation emerged when variables concerning work characteristics (inter alia, working hours) and demographic characteristics were controlled for. Using a domains-of-life approach, our study explores the importance of work-related variables in explaining overall life satisfaction in 28 EU countries, 2011-2012.…”
Section: 1mentioning
confidence: 94%
“…For example, Rode and Near (2005) contend that it is not job satisfaction that impacts on overall life satisfaction; rather, the relationship will appear when constraints, opportunities and activities associated with the work domain influence the constraints, opportunities and activities experienced in other life domains. One such crucial linkage between the domains is that between the work and the family/home, which has been amply demonstrated in the literature on work-life balance.…”
Section: Working Conditions and Life Satisfactionmentioning
confidence: 99%
“…Diener et al 1999;Rode and Near 2005;Wallace et al 2007), as are the explanations of the mechanisms that generate the link between working conditions and life satisfaction. We therefore take a stepwise approach to the question.…”
Section: Analytic Strategy and Hypothesesmentioning
confidence: 99%
“…The direction of influence is assumed to be from the specific to the general, in this case from satisfaction with specific life domains (e.g., work) to overall life satisfaction, or from the "bottom-up" (e.g., Brief et al 1993). There is some controversy as to whether domain satisfactions predict life satisfaction or whether life satisfaction predicts satisfaction in the various domains of life through some process of generalization (so-called "top-down theories"; Judge and Watanabe 1993), but recent longitudinal research has found support of the bottom-up perspective, even after controlling for the effects of personality and living and working conditions (Rode 2004;Rode and Near 2005). Thus, our model includes a positive link between job and life satisfaction, after taking into account the effects of work and family conflict.…”
Section: Relationship Between Job Satisfaction and Life Satisfactionmentioning
confidence: 99%
“…Spillover may also be indirect, due to the effects of role conflict resulting from work demands on fixed resources, such as time and energy (Greenhaus and Powell 2003;Staines 1980;Voydanoff 2002), which then reduces life satisfaction. Indirect attitude spillover can also result when working conditions or demands directly affect nonwork conditions such as geographic location, living arrangements, and social networks and activities, which in turn affect nonwork attitudes (e.g., Campbell et al 1976;Near et al 1980;Rode and Near 2005).…”
Section: Life Satisfaction As a Mediator Between Job Satisfaction Andmentioning
confidence: 99%